Development of a Glucocorticoid Toxicity Index (GTI) using multicriteria decision analysis. Issue 3 (29th July 2016) - Miloslavsky, Eli M; Naden, Ray P; Bijlsma, Johannes W J; Brogan, Paul A; Brown, E Sherwood; Brunetta, Paul; Buttgereit, Frank; Choi, Hyon K; DiCaire, Jean-Francois; Gelfand, Jeffrey M; Heaney, Liam G; Lightstone, Liz; et al.
Abstract : Objectives: To develop a Glucocorticoid Toxicity Index (GTI) to assess glucocorticoid (GC)-related morbidity and GC-sparing ability of other therapies. Methods: Nineteen experts on GC use and outcome measures from 11 subspecialties participated. Ten experts were from the USA; nine from Canada, Europe or Australia. Group consensus methods and multicriteria decision analysis (MCDA) were used. A Composite GTI and Specific List comprise the overall GTI. The Composite GTI reflects toxicity likely to change during a clinical trial. The Composite GTI toxicities occur commonly, vary with GC exposure, and are weighted and scored. Relative weights for items in the Composite GTI were derived by group consensus and MCDA. The Specific List is designed to capture GC toxicity not included in the Composite GTI. The Composite GTI was evaluated by application to paper cases by the investigators and an external group of 17 subspecialists. Results: Thirty-one toxicity items were included in the Composite GTI and 23 in the Specific List. Composite GTI evaluation showed high inter-rater agreement (investigators κ 0.88, external raters κ 0.90). To assess the degree to which the Composite GTI corresponds to expert clinical judgement, participants ranked 15 cases by clinical judgement in order of highest to lowest GC toxicity. Expert rankings were then compared with case ranking by the Composite GTI, yielding excellent agreement (investigators weighted κ 0.87, external raters weighted κ 0.77). Conclusions: We describe the development and initial evaluation of a comprehensive instrument for the assessment of GC toxicity.